Data protection in schools (Journal of Parents and Teachers, 2014)
Personal data whose aim is the identification of an individual, are every time more vulnerable to privacy, therefore schools and other educative centres must guarantee the right of controlling personal data to students, families and staff. Under the principles of data protection: quality, consent and security; the person in charge of the file must not give personal information to a third person.
Keywords: school organization; data protection; security; privacy; data management.